PEMEROLEHAN MULTILINGUALISME PADA ANAK USIA DINI MELALUI MEDIA YOUTUBE UENO FAMILY JAPAN - Apriliani, Delia; Casim, Casim (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2025)
Language development plays a very important role in children's education because it is related to communication, emotional expression, and cognitive development. In Indonesian society, which has a variety of languages, children are often introduced to various languages from an early age, including local languages, the national language, and foreign languages. The family is an important environment for learning. Parents play a role in guiding children to fulfill their developmental obligations, including language development. This study describes how parental tasks influence children's individual development. This study aims to explain the influence of parents on the acquisition of multilingualism in children aged three years and nine months. This study focuses on how parental tasks support and accelerate children's proficiency in mastering three languages. This study uses a qualitative approach, namely document study. The respondent in this study is a three-year-old child named Ueno Ritsuki. The data analysis obtained in this study is in the form of conversations. The data source for this study is the utterances of a child named Ueno Ritsuki, who is three years and five months old.